Temporal and Spatial Dynamics of Different Interictal Epileptic Discharges: A Time-Frequency EEG Approach in Pediatric Focal Refractory Epilepsy - Jabran, Younes; Mahmoudzadeh, Mahdi; Martinez, Nicolas; Heberlé, Claire; Wallois, Fabrice; Bourel-Ponchel, Emilie (Frontiers in Neurology, 2020)
Objective: Characterization of the spatial and temporal dynamics of interictal epileptic discharges (IED) using time-frequency analysis (TFA) and electrical-source localization (ESL). Methods: TFA was performed on IED (spikes, spike waves, and polyspike waves) recorded by high-density-EEG (HD-EEG) in 19 refractory focal epileptic children. Temporal modulations related to IEDs were analyzed in a time window around the IED peaks [-1000 to 1000 ms]. Spatial modulations were analyzed by ESL in the time-frequency and time domains. Results: IED were associated with complex power spectral modulations. We observed increases in power spectrum (IPS) patterns specific to IED type. For spikes, the TFA pattern consisted of an IPS (-100 to +100 ms, 4-50 Hz). For spike waves, the IPS was followed by a second IPS (+100 to +400 ms, 4-10 Hz), corresponding to the slow wave. IPS patterns were preceded (-400 to -100 ms, 4-40 Hz) and followed (+100 to +400 ms) by a decrease in the power spectrum (DPS) (n=8). For 14 out of 19 patients, at least one ESL method was concordant with the epileptogenic area. For the remaining five patients, all of them had temporal epilepsies. ESL in the time-frequency domain (DPS/IPS) provided concordant (n=6) or complementary (n=4) information to the ESL in the time domain concerning the epileptogenic zone. ESL in time-frequency domain (DPS/IPS) was the only method to provide concordant information concerning the epileptogenic zone in three patients. Significance: TFA demonstrates complex time-frequency modulations of the neuronal networks around IED, suggesting that the pathological mechanisms are initiated well before onset of the classical hyper-synchronization of the IED. Combining time and time-frequency analysis of the ESL provides complementary information to define the epileptogenic zone in refractory focal epilepsy.